Filosofia da educação: do ideário educacional de Rousseau à sua atualização e recepção na Escola nova - COSTA, Danielle Lima (2014)
This thesis aims to discuss, in the field of philosophy of education, the thought of JeanJacques Rousseau on education through the work Emile or Education (1762), analyzing the principles that influenced the so-called New School, as an educational trend XX century. Started from the hermeneutics of theoretical propositions about the relationship between education, subject and subjectivity, based on the historical and philosophical context of the modern age as material and cultural ambience that allowed the emergence of a plurality of ideas about the new paradigm on the design of modern man. Then the pedagogical project were discussed in Rousseau, in the above work. Finally, the discussion of the principles of influencers Rousseauvian assumptions for the educational proposal of the New School in the twentieth century, located specifically in the first two phases of development of this educational trend, from the selection of two lead authors of each step. For this, we used the classification Palácios (1984), namely: the romantic stage, with Pestalozzi and Froebel; and the second methodological deepening step with Ferriere and John Dewey. The analysis path out fabric, yet, beneath the debate that permeates the philosophical background of the New School educational concept expressed in the clash between pedagogy and pedagogy of the essence of existence. Justified this search by topic relevance of education and its necessary philosophical reflection, given that sometimes certain contemporary studies has been fixed in the tenders and or methodological techniques devoid of philosophical fundamental debate on principles and foundations. Expected to contribute in an interdisciplinary way through reflections within the philosophy and education, from a deeper debate on the principles underpinning the pedagogical concepts and their educational intentions.